Pengaruh Jenjang Karir, Kemampuan Kerja, Dan Penghargaan Perusahaan Terhadapkinerja Karyawan Pada Pt. Bumi Menara Internusa Dampit Kabupaten Malang - Alif Taufan Wijaya; Abdul Kodir Djaelani; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2021)
ABSTRACTThis research was conducted at PT. Bumi Menara Internusa Dampit. The purpose of this study was to examine and analyze the effect of Carrier Path,, Work Ability and Company Award on Employee Performance of PT. Bumi Menara Internusa Dampit.The variables used are Carrier Path,, Employee Ability and Company Award as independent variables, while the Employee Performance variable as the dependent variable. The sample used in this study was 63 employees of PT. Bumi Menara Internusa Dampit uses sampling random method. Data collection methods by collecting primary and secondary data. The analysis used includes instrument testing, classic assumption tests, normality tests, multiple linear regression, hypothesis testing and coefficient of determination.The results showed that the Carrier Path variable significantly affected the Employee Performance of PT. Bumi Menara Internusa Dampit, while the Company Award variable does not significantly influence the Employee Performance of PT. Bumi Menara Internusa Dampit..Keywords : Carrier Path, Work Ability, Company Award and Employee Performance